(untitled) (Colombia Medica, 2013)
Introduction: The pathophysiology of cerebral ischemia is essential for early diagnosis, neurologic recovery, the early onset of drug treatment and the prognosis of ischemic events. Experimental models of cerebral ischemiac an be used to evaluate the cellular response phenomena and possible neurological protection by drugs. Objective: To characterize the cellular changes in the neuronal population and astrocytic response by the effect of Dimethyl Sulfoxide (DMSO) on a model of ischemia caused by cerebral embolism. Methods: Twenty Wistar rats were divided into four groups (n= 5). The infarct was induced with α-bovinethrombin (40 NIH/U). The treated group received 90 mg (100 µL) of DMSO in saline (1:1 v/v) intraperitoneally for 5 days; ischemic controls received only NaCl (placebo) and two non-ischemic groups (simulated) received NaCl and DMSO respectively. We evaluated the neuronal (anti-NeuN) and astrocytic immune-reactivity (anti-GFAP). The results were analyzed by densitometry (NIH Image J-Fiji 1.45 software) and analysis of variance (ANOVA) with the Graph pad software (Prism 5). Results: Cerebral embolism induced reproducible and reliable lesions in the cortex and hippocampus (CA1). similar to those of focal models. DMSO did not reverse the loss of post-ischemia neuronal immune-reactivity, but prevented the morphological damage of neurons, and significantly reduced astrocytic hyperactivity in thesomato-sensory cortex and CA1 (P <0.001). Conclusions: The regulatory effect of DMSO on astrocyte hyperreactivity and neuronal-astroglial cytoarchitecture, gives it potential neuroprotective properties for the treatment of thromboembolic cerebral ischemiain the acute phase.